2019
DOI: 10.1021/acs.chemmater.9b01937
|View full text |Cite
|
Sign up to set email alerts
|

Developing Precursor Chemistry for Atomic Layer Deposition of High-Density, Conformal GeTe Films for Phase-Change Memory

Abstract: Atomic layer deposition (ALD) of phase-change materials has been suggested as the most feasible technique for the construction of high-aspect-ratio architectures required for ultrahigh-density phase-change random access memory (PcRAM). The recent advances in the ALD technique have established the foundations for the formation of conformal Ge–Te or Ge–Sb–Te films, but their electrical performance as a phase-change memory device has been rarely reported, especially with prolonged cycles. This study introduced Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…A faster growth rate of ∼97 ng·cm –2 ·cy –1 was achieved on the ST surface . All of the GT films grown on the three types of substrate were amorphous, which was consistent with the high crystallization temperature (180–190 °C) of the GT layer . The amorphous films on the three different types of the substrate had low RMS roughness (∼0.5 nm); thus, there should be no difference in the growth rate induced by the roughness effect.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…A faster growth rate of ∼97 ng·cm –2 ·cy –1 was achieved on the ST surface . All of the GT films grown on the three types of substrate were amorphous, which was consistent with the high crystallization temperature (180–190 °C) of the GT layer . The amorphous films on the three different types of the substrate had low RMS roughness (∼0.5 nm); thus, there should be no difference in the growth rate induced by the roughness effect.…”
Section: Resultssupporting
confidence: 63%
“…The Ge­(II) precursor, Ge­(guan)­NMe 2 , contains two anionic ligands: the dimethylamino and bidentate guanidinate groups [(i) in Figure a]. The previous study has shown that the high thermal stability of the Ge precursors enabled the ALD of the GT film at high temperatures up to 170 °C . Te­(SiMe 3 ) 2 was coinjected with NH 3 to form H 2 Te [(iii) in Figure a] and to facilitate the dissociation of the guanidinate ligand via protonation, as confirmed in the previous density functional theory study …”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…As a storage medium, Phase-Change RAM (PCRAM) is mainly based upon chalcogenide (Group VI) and pnictide (Group V) elements, in the form of Germanium-antimony-tellurium (GST) alloys such as Ge 2 Sb 2 Te 5 (usually abbreviated as GST) and compositional variations of GeSb [ 101 ], GeTe [ 102 ], InSbTe [ 103 ], InGeTe [ 104 ], InSbGe, AgInSbTe [ 105 ], GeSbSeTe, GeSbReBi, SiSbTe [ 106 ], and SbTe [ 107 ]. The particularly relevant feature of these compositions, here, is that their electrical/optical properties, such as their electrical resistivity and optical reflectivity, differ sharply between their crystalline state (with a long-range atomic order) and their amorphous state (with a short-range atomic order).…”
Section: Logic In Phase-change Rammentioning
confidence: 99%